Syngeneic cardiac and bone marrow stromal cells display tissue-specific microRNA signatures and microRNA subsets restricted to diverse differentiation processes. - Viviana Meraviglia (Public Library of Science (PLoS), 2014)
MicroRNAs are key modulators at molecular level in different biological processes, including determination of cell fate and differentiation. Herein, microRNA expression profiling experiments were performed on syngeneic cardiac (CStC) and bone marrow (BMStC) mesenchymal stromal cells cultured in standard growth medium and then in vitro exposed to adipogenic, osteogenic, cardiomyogenic and endothelial differentiation media. Analysis identified a tissue-specific microRNA signature composed of 16 microRNAs that univocally discriminated cell type of origin and that were completely unaffected by in vitro differentiation media: 4 microRNAs were over-expressed in cardiac stromal cells, and 12 were overexpressed or present only in bone marrow stromal cells. Further, results revealed microRNA subsets specifically modulated by each differentiation medium, irrespective of the cell type of origin, and a subset of 7 microRNAs that were down-regulated by all media with respect to growth medium. Finally, we identified 16 microRNAs that were differentially modulated by the media when comparing the two tissues of origin. The existence of a tissue-specific microRNA signature surviving to any differentiation stimuli, strongly support the role if microRNAs determining cell identity related to tissue origin. Moreover, we identified microRNA subsets modulated by different culture conditions in a tissue-specific manner, pointing out their importance during differentiation processes.